An ergonomic perspective of user need on physio-treadmill (PhyMill) criteria: knowledge and awareness of cerebral palsy among future parents - Rabiatul Aisyah, Ariffin; Mohd Azrul Hisham, Mohd Adib; Nurul Shahida, M. S.; Narimah, Daud; Nur Hazreen, Mohd Hasni (IOP Publishing, 2020)
Cerebral palsy (CP) is the most common childhood disability. This study focused to explore the future parents' perspective on the Physio-Treadmill (PhyMill) for the kid with CP, particularly how ergonomics influences the product. The study was carried out by a quantitative survey and involves 55 participants. The participants have answered a self-administered which consists of general information, knowledge awareness on cerebral palsy, product criteria and opinions. The result shows about 55% of participants have a poor level of awareness and 69% of participants have zero knowledge of CP treatment. However, based on the product criteria, most of the participants agreed, the present PhyMill shows well in functionality. Hence, this study emphasized the lack of awareness and knowledge of the disease and treatment among future parents. Besides, the PhyMill need to improve from the potential user recommendation as ergonomics consideration on medical devices.